Peningkatan Hasil Belajar Siswa Menggunakan Model Talking Stick di Sekolah Dasar - Vivi Uvaira Hasibuan; Fitriyani Fitriyani (Keguruan, 2020)
The objectives of this study are: 1) to find out the application of the talking stick model to improve the understanding of fourth grade students at SDN 101930 Perbaungan 2) to find out the increase in understanding after the implementation of the talking stick method in grade IV SDN 101930 Perbaungan. The subjects in this study were fourth grade students, totaling 20 students consisting of 12 male students and 8 female students. The research method used in this study is the classroom action research method (CAR) consisting of four stages in each cycle consisting of planning, implementation, observation, and reflection. This research consisted of two cycles, cycle I and cycle II. Data collection techniques used in this study are interviews, observation, documentation, and tests. The results showed that: 1) the application of the talking stick model could be implemented well, as evidenced by the results of observing teacher activities that increased from a value of 79.3 (enough) in the first cycle to 91.4 (very good) in the second cycle. The results of observing student activities got a final score of 78.8 (enough) in the first cycle, increasing to 94 (excellent) in the second cycle. 2) the increase in students' understanding after the implementation of the talking stick model increased from 25% of students who completed the pre-cycle, in the first cycle increased to 57.5% (enough) and in the second cycle increased to 80% (good).